The Impact of Collaborative E-Learning on the Learning Motivation of Female Doctoral Students: A Case Study of Students in the Course on Employing Technology in Education - Affouneh, Saida Jaser; Drawshi, Eman Omar; Rabi, Areej Helmi; Zoubi, Reem Hani; Miari, Sajida Sobhi; Salame, Salwa Fawze; Drawshy, Sana Fwaz; Nassar, Suheir Huleihel; Azem, Sireen Mahmood; Drawshi, Sabrin Nor; Asadi, Safa AbdelKareem; Dabbah, Najwa Zeed; et al. (Journal of Educational and Psychological Sciences, 2025)
The study aimed to explore the impact of electronic collaborative learning on the learning motivation of PhD students: A case study of students enrolled in the "Technology Integration in Teaching and Learning" course. The study adopted a qualitative research approach, utilizing semi-structured interviews. The study population consisted of all 14 students in the course, at An-Najah National University, during the academic year 2024–2025. The interviews were conducted via the “Zoom” application, recorded, transcribed, and analyzed to derive findings. The results revealed that electronic collaborative learning positively contributed to enhancing students’ motivation by providing them with an interactive experience that encouraged active participation and group learning. Tools such as "Zoom" and breakout rooms proved instrumental in improving technical skills and fostering social and academic relationships among the students. Despite these benefits, challenges were identified, including poor internet connectivity, varying levels of technical proficiency, and unequal distribution of tasks within the groups. The findings highlighted the importance of social interaction and psychological support among students, which helped build self-confidence and overcome obstacles. The researchers recommend strengthening technological infrastructure, organizing workshops to enhance technical skills, and ensuring equitable task distribution within groups. Furthermore, it emphasizes the necessity of integrating instructional strategies that balance individual and group learning, with a focus on critical and creative thinking, as well as enhancing social interaction to improve the quality of the learning process and achieve sustainable academic goals.